Citra Politik Kandidat Walikota Semarang dalam Instagram: Analisis Dramaturgi pada Pilwakot Semarang 2020 - Risky Adi Pamungkas; Muhammad Adnan (Universitas Indo Global Mandiri, 2023)
This article aims to analyze the political image of Hendrar Prihadi (Hendi), incumbent mayoral candidate of Semarang 2020 election shown on Instagram @hendrarprihadi in the midst of covid-19 pandemic. If most candidates concoct political slogans and deliver campaign promises, Hendi’s Instagram portrays more amusing content with a minimum amount of campaign messages. Dramaturgy theory used to analyze framing processes on Instagram as frontstage, and what backstage and offstage factors could affect this single candidate manage to get 91,4% of votes, even though activists consider election in the midst of pandemic as less humane, and single candidate could lower voters’ turnover. Qualitative analysis data collected from interviews and articles shows that amusing content on Hendi’s Instagram designed to pacify the public affected by covid-19, followers are easily extracted by amusing content, and as a method to sheer away from sensitive political issues. Backstage, although Semarang reported as the highest contributor of covid-19 cases in Indonesia, and numbers of rule violation campaigns, candidate characteristic, leadership, incumbent status, and also relation with public and political figure be the several things making candidate’s political image more stable, affecting candidate winning the 2020 Semarang Mayoral Election.